Evaluation of Women's Empowerment in a Community-Based Human Papillomavirus Self-Sampling Social Entrepreneurship Program (Hope Project) in Peru: A Mixed-Method Study - Shin, Michelle B.; Garcia, Patricia J.; Dotson, Mary Elizabeth; Valderrama, María; Chiappe, Marina; Ramanujam, Nimmi; Krieger, Marlee; Ásbjörnsdóttir, Kristjana; Barnabas, Ruanne V.; Iribarren, Sarah J.; Gimbel, Sarah (Frontiers in Public Health, 2022)
Introduction Understanding community women's relational and financial empowerment in social entrepreneurship could be the key to scaling up community-based human papillomavirus (HPV) self-sampling programs in low- and middle-income countries. The Hope Project, social entrepreneurship in Peru, trains women (Hope Ladies) to promote HPV self-sampling among other women in their communities. This study aims to evaluate the Hope Ladies' relational and financial empowerment after participating in the program. Materials and Methods We evaluated the Hope Ladies' experiences of empowerment in social entrepreneurship using a parallel convergent mixed methods design. The Hope Ladies participated in semi-structured in-depth interviews (n = 20) and an eight-questions five-point Likert scale survey that evaluated their relational (n = 19)/financial (n = 17) empowerment. The interview and the survey questions were developed using three empowerment frameworks: Kabeer's conceptual framework, International Center for Research on Women's economic empowerment indicators, and the Relational Leadership Theory. Deductive content analysis was used to evaluate the interviews with pre-determined codes and categories of empowerment. Descriptive statistics were used to analyze the survey results. Qualitative and quantitative data were integrated through a cross-case comparison of emergent themes and corresponding survey responses during the results interpretation. Results All Hope Ladies reported experiencing increased empowerment in social entrepreneurship. Interviews: The women reported challenges and improvement in three categories of empowerment: (1) resources (balancing between household and Hope Lady roles, recognition from the community as a resource, camaraderie with other Hope Ladies); (2) agency (increased knowledge about reproductive health, improved confidence to express themselves, and ability to speak out against male-dominant culture); and (3) achievement (increased economic assets, improved ability to make financial decisions, and widened social network and capital, and technology skills development). Survey: All (100%) agreed/totally agreed an increase in social contacts, increased unaccompanied visits to a healthcare provider (86%), improved confidence in discussing reproductive topics (100%), improved ability to make household decisions about money (57% pre-intervention vs. 92% post-intervention). Conclusions The Hope Ladies reported improved relational and financial empowerment through participating in community-based social entrepreneurship. Future studies are needed to elucidate the relationship between empowerment and worker retention/performance to inform the scale-up of HPV self-sampling social entrepreneurship programs.